Psychometric testing of the Family‐Carer Diabetes Management Self‐Efficacy Scale. (6th November 2017) - Wichit, Nutchanath; Mnatzaganian, George; Courtney, Mary; Schulz, Paula; Johnson, Maree
Abstract: The aim of this study was to develop and test the construct and content validity, internal consistency of the Family‐Carer Diabetes Management Self‐Efficacy Scale (F‐DMSES). A sample of 70 Thai individuals who cared for those living with type 2 diabetes mellitus (T2DM) in a rural community in Thailand was included in the study. Data were collected by a questionnaire survey in January 2014. The F‐DMSES was initially derived from the DMSES, with subsequent forward and backward translations from and to English and Thai languages. The psychometric properties (content, construct and internal consistency) of the Thai version were explored using the Content Validity Index approach, exploratory factor analysis and Cronbach's alpha test. The F‐DMSES initially designed with 20 items was reduced to 14 items within four factors (general diet and blood glucose monitoring, medications and complications, diet in differing situations, and weight control and physical activities), and explained 72.2% of the total variance in overarching construct. Internal consistency was supported (α = 0.89). The F‐DMSES was also able to measure change over time following an intervention, with an effect size of 0.9. The F‐DMSES is a valid and reliable self‐administered instrument that measures the diabetes management self‐efficacy of family‐carers of individuals with T2DM. This instrument can be used in practice and clinical trials to assess the impact of family‐carers on the health outcomes of individuals with T2DM.